(untitled) (Physical Education, Health and Social Sciences, 2025)
Introduction and background: Intrauterine growth restriction is a growth of fetal disorder in which the fetal weight is below the normal weight (below then ten percent) for the analogous gestational age. IUGR is the leading contributor to perinatal morbidity and mortality. The majority of females have a gestational age of 34 weeks. The objective of our study is to evaluate fetal growth restriction on ultrasound. Materials and methods: A total of 100 cooperative responding patients were included in the study and the study was carried out in Fatima Medical Center Rahim Yar Khan. Results: This observational evaluated fetal growth restriction (FGR) using ultrasound measurements—HC, AC, BPD, FL, and P.I index—across gestational ages of 10–36 weeks. Executed at Fatima Medical Center, Rahim Yar Khan, it involved 50 singleton pregnancies with normal uterine conditions, using availability sampling. Exclusions were multiple pregnancies, uncooperative patients, and conditions like PCOS. Ultrasound scans were performed with a LOGIQ E9 Rev 5 curve linear transducer and FGR was assessed by a radiologist based on biometric parameters. Conclusions: Ultrasound plays an indispensable role in the detection, evaluation, and ongoing monitoring of fetal growth restriction (FGR). Its non-invasive nature, widespread availability, and real-time imaging capabilities make it the most reliable tool for assessing fetal development across all three trimesters. Key words: IUGR, Fetus, third trimester, Ultrasound, Restriction, gestational, perinatal, Mortality, morbidity.